3D imaging of biological specimen using MS. (October 2015) - Fletcher, John S
Imaging MS can provide unique information about the distribution of native and non-native compounds in biological specimen. MALDI MS and secondary ion MS are the two most commonly applied imaging MS techniques and can provide complementary information about a sample. MALDI offers access to high mass species such as proteins while secondary ion MS can operate at higher spatial resolution and provide information about lower mass species including elemental signals. Imaging MS is not limited to two dimensions and different approaches have been developed that allow 3D molecular images to be generated of chemicals in whole organs down to single cells. Resolution in the z-dimension is often higher than in x and y, so such analysis offers the potential for probing the distribution of drug molecules and studying drug action by MS with a much higher precision – possibly even organelle level.